Pancreatic Ductal Adenocarcinoma is Spread to the Peripancreatic Soft Tissue in the Majority of Resected Cases, Rendering the AJCC T-Stage Protocol (7th Edition) Inapplicable and Insignificant: A Size-Based Staging System (pT1: <= 2, pT2: > 2-<= 4, pT3: > 4 cm) is More Valid and Clinically Relevant - BAĞCI ÇULÇİ, PELİN (SPRINGER, 2016)
Most studies have failed to identify any prognostic value of the current T-stage protocol for pancreatic ductal adenocarcinoma (PDAC) by the American Joint Committee on Cancer and the Union for International Cancer Control unless some grouping was performed. To document the parameters included in this T-stage protocol, 223 consecutive pancreatoduodenectomy specimens with PDAC were processed by a uniform grossing protocol. Peripancreatic soft tissue (PST) involvement, the main pT3 parameter, was found to be inapplicable and irreproducible due to lack of a true capsule in the pancreas and variability in the amount and distribution of adipose tissue. Furthermore, 91 % of the cases showed carcinoma in the adipose tissue, presumably representing the PST, and thus were classified as pT3. An additional 4.5 % were qualified as pT3 due to extension into adjacent sites. The T-stage defined as such was not found to have any correlation with survival (p = 0.4). A revised T-stage protocol was devised that defined pT1 as 2 cm or smaller, pT2 as > 2-4 cm, and pT3 as larger than 4 cm. This revised protocol was tested in 757 consecutive PDACs. The median and 3-year survival rates of this size-based protocol were 26, 18, 13 months, and 40 %, 26 %, 20 %, respectively (p < 0.0001). The association between higher T-stage and shorter survival persisted in N0 cases and in multivariate modeling. Analysis of the Surveillance, Epidemiology, and End Results database also confirmed the survival differences (p < 0.0001). This study showed that resected PDACs are already spread to various surfaces of the pancreas, leaving only about 4 % of PDACs to truly qualify as pT1/T2, and that the current T-stage protocol does not have any prognostic correlation. In contrast, as shown previously in many studies, size is an important prognosticator, and a size-based T-stage protocol is more applicable and has prognostic value in PDAC.
Keywords: SINGLE-INSTITUTION EXPERIENCE; RANDOMIZED CONTROLLED-TRIAL; LONG-TERM SURVIVAL; LYMPH-NODE RATIO; COMMON BILE-DUCT; PROGNOSTIC-FACTORS; PANCREATICODUODENECTOMY SPECIMENS; ADJUVANT CHEMOTHERAPY; CURATIVE RESECTION; SURGICAL RESECTION